Phase formation and impurity effects in Ar+ ion irradiated Mo/Si thin film bilayer system. (6th December 2012) - Singh, Ch. Kishan; Ilango, S.; Dash, S.; Tyagi, A. K.
<x xml:space="preserve">Abstract</x> We report a dose‐dependent phase evolution in Mo/Si bilayer system upon Ar+ ion beam irradiation and subsequent flash annealing at 800 °C for 60 s. Micro‐structural characterization with Grazing Incidence X‐ray Diffraction and Raman scattering reveals a dose‐dependent nucleation of polymorphic phases occurring at the amorphized interface region. The ion beam mixing process has been investigated by Secondary Ion Mass Spectrometry and Rutherford Backscattering Spectrometry. While low ion doses favour nucleation of only metastable MoSi2 phase, co‐existence of polymorphic phases are observed at high ion doses. The persistence of such polymorphic phases even after a high‐temperature anneal for high dose implanted specimen is indicative of phase retardation. The phase retardation of h‐MoSi2 to t‐MoSi2 is accounted in terms of nucleation and growth process. Copyright © 2012 John Wiley & Sons, Ltd.